Arteterapia: una experiencia de grupos de apoyo a mujeres - Omenat García, Montse (Arteterapia. Papeles de arteterapia y educación artística para la inclusión social, 2006)
We present here an experience of support s to women across a art therapy group, developed from 2002. There is described the origin of this project, developed in a zone close to Barcelona for women who were living through a situation of particular diffi culty, as mistreatment or isolation and in enough occasions also in contact with alcoholism. Its aims and its evolution throughout the years are described here and its condition and current balance are evaluated.